PENGARUH MODEL PEMBELAJARAN DAN KONSEP DIRI TERHADAP HASIL BELAJAR IPA - Jatmiko, Agus (Biosfer: Jurnal Tadris Biologi, 2017)
This research was intended to reveal the effect of instructional model and self-concept on learning achievement of Science. The research use experimental method with 2X2 factorial design and was carried out at SMP Negeri 24 Bandar Lampung with sample of 44 students. ANAVA applied to analyzed the data obtained at the significant level of 0,05.The results of this research are: (1) student’s learning achievement of Science who uses by Learning Cycle model is higher than Contextual Teaching and Learning model; (2) There is an interaction effect between instructional model and self-concept on student’s learning achievement of Science; (3) student’s learning achievement of Science who uses by Learning Cycle model is higher than Contextual Teaching and Learning model with positive self-concept; 4) student’s learning achievement of Science who uses by Learning Cycle model is lower than Contextual Teaching and Learning model with negative self-concept.